Medical Treatment of Heart Failure with Reduced Ejection Fraction in the Elderly - Ivan Milinković; Marija Polovina; Andrew JS Coats; Giuseppe MC Rosano; Petar M Seferović (Cardiac Failure Review)
The aging population, higher burden of predisposing conditions and comorbidities along with improvements in therapy all contribute to the growing prevalence of heart failure (HF). Although the majority of trials have not demonstrated age-dependent heterogeneity in the efficacy or safety of medical treatment for HF, the latest trials demonstrate that older participants are less likely to receive established drug therapies for HF with reduced ejection fraction. There remains reluctance in real-world clinical practice to prescribe and up-titrate these medications in older people, possibly because of (mis)understanding about lower tolerance and greater propensity for developing adverse drug reactions. This is compounded by difficulties in the management of multiple medications, patient preferences and other non-medical considerations. Future research should provide a more granular analysis on how to approach medical and device therapies in elderly patients, with consideration of biological differences, difficulties in care delivery and issues relevant to patients’ values and perspectives. A variety of approaches are needed, with the central principle being to ‘add years to life – and life to years’. These include broader representation of elderly HF patients in clinical trials, improved education of healthcare professionals, wider provision of specialised centres for multidisciplinary HF management and stronger implementation of HF medical treatment in vulnerable patient groups.